Monetary thinking of the population of the Republic of Belarus - Haurylik, Aksana N. (Journal of the Belarusian State University. Sociology, 2019)
The need to study monetary thinking of the population is caused both by process of reforming the economic sphere, and the transformation of public consciousness. The article presents the results of complex research of features of monetary thinking of the population of Republic of Belarus, which was conducted between July 2016 to March 2017 with application of qualitative and quantitative research methods: deep interview, expert survey and questionnaires. The data obtained are supplemented by the information contained in the works of the Belarusian scientists, as well, the dynamics of the population of values based on a comparison of the results of a questionnaire survey, conducted in 2017, and the European Values Study, conducted in 2008–2009. Public perceptions were revealed about the money as a subject of social relations; predominant type of economic behaviour; attitude to entrepreneurs and financial institutions. It was also established differences in monetary thinking of different categories of population.
Keywords: monetary thinking; money; type of economic behaviour; trust to financial institutions; business